The political economy of China's oil strategy in Africa - Sterley, Carla (My University, 2014)
China’s rising role and involvement in Africa has resulted in an increasing amount of focus and interest on the continent, specifically with regards to its relations with various individual African states and the West. It has been argued that China and the West are locked in a political, economic and diplomatic confrontation on the continent, intensified by the need to gain access to natural resources, especially oil. This study analysis the behaviour of Chinese oil companies in Africa, with specific focus on whether their investment patterns tend directly to confront established Western interests, or whether they simply position them as economic competitors. This is tested through a study of two cases, the first of Sudan which focuses on the availability of reserves in the form of abandoned facilities by Western oil companies and the second of Equatorial Guinea which concentrates on new investment opportunities in the form of newly discovered offshore oil reserves. It is determined that Chinese oil companies avoid political confrontation with the West through avoiding direct involvement with United States-based oil companies and by co-operating with the host government and other non-Western oil companies operating within the same oil-rich states in Africa.